Hiya. I'm going to rewrite the second equation.
By subtracting 5x by both sides, I'll be able to have y by itself:
-y=-5x+13
I'm going to then divide both sides by -1 to get:
y=5x-13.
Then, I'm going to plug that equation into the first equation
3x+2(5x-13)=39
Factor:
3x+10x-26=39
Combine like terms:
13x=65
Divide both sides by 13 to get x by itself to get x=5
Plug this back into the equation of y=5x-13
y=5(5)-13 to get y=12
Answer:
58%
Step-by-step explanation:
47/81 x 100%
≈ 58%
Hope it helps : )
Answer:
-14
Step-by-step explanation:
Answer:
7/2 = 35/10
3/5 = 6/10
Step-by-step explanation:
To get a common denominator of 10, simply multiply the current denominator by any number to equal 10. The first fraction has a denominator of 2. If we divide 10 by 2, we get the answer 5. This means 2 can be multiplied by 5 to get a denominator of 10. However, what we do to the denominator we must also do to the numerator (multiply by 5).
7/2
7 × 5 / 2 × 5
35/10
3/5
3 × 2 / 5 × 2
6/10
brainliest pls
Answer:
thousands place
Step-by-step explanation:
Have a nice day